Determination of Si(Li) detector efficiency by experimental and Monte Carlo simulation methods. (1st March 2021) - Zadehrafi, M; Luca, A; Ioan, M-R
Abstract: In this study, a Si(Li) detector was modeled by MCNP (Monte Carlo n-particle) code and its efficiency was estimated by Monte Carlo simulation in the photon energy range of 5.9–59.54 keV. Experimental measurements using 55 Fe, 57 Co, and 241 Am radioactive standard sources were performed for validation of the applied simulation code. The primary results of the simulation were compared with the experimental ones and considerable discrepancies were observed, especially in the low energy region. Since the dead layers' thicknesses are not always precisely provided by the manufacturer and even can change during detector aging, they were assumed as the cause of these discrepancies (front dead layer's thickness being a critical parameter for low energy photons). After adjusting the thicknesses of the front and rear dead layers in a step-by-step procedure, a reasonable agreement was achieved between the simulated and experimental results. The results of this study indicate that if performing an experiment by the detector is difficult for any reason in some energies, one can rely on the MCNP code as an operational tool by interpolation or extrapolation of the available experimental efficiency data (in low energy region).